2016
DOI: 10.1116/1.4960356
|View full text |Cite
|
Sign up to set email alerts
|

Optical constants, band gap, and infrared-active phonons of (LaAlO3)0.3(Sr2AlTaO6)0.35 (LSAT) from spectroscopic ellipsometry

Abstract: Using spectroscopic ellipsometry, the authors determined the optical constants (complex dielectric function) for (LaAlO3)0.3(Sr2AlTaO6)0.35 (LSAT) from 0.01 to 6.5 eV. Above 0.5 eV, the data were described with a sum of two Tauc-Lorentz oscillators and two poles. A direct gap of 5.8 ± 0.1 eV was found. An Urbach tail extends to even lower photon energies and makes the crystal opaque above 4.8 eV. Using Fourier-transform infrared ellipsometry, the lattice dynamics was studied. Nine pairs of transverse/longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…coefficient as a function of photon energy obtained with the multi-oscillator model developed for the LSAT substrate. Our results are in good agreement with previous results [30]; however, by characterizing the substrate further in the VUV range, we have more complete picture of the optical properties of this material. Upon closer examination of the absorption coefficient in the range α from 2×10 3 cm −1 to 45×10 3 cm −1 , we find that plotting the square root of absorption versus photon energy results again in stepwise linear behavior, which as stated above for STO is indicative of an indirect bandgap for LSAT.…”
Section: Lanthanum Strontium Aluminum Tantalatesupporting
confidence: 92%
See 2 more Smart Citations
“…coefficient as a function of photon energy obtained with the multi-oscillator model developed for the LSAT substrate. Our results are in good agreement with previous results [30]; however, by characterizing the substrate further in the VUV range, we have more complete picture of the optical properties of this material. Upon closer examination of the absorption coefficient in the range α from 2×10 3 cm −1 to 45×10 3 cm −1 , we find that plotting the square root of absorption versus photon energy results again in stepwise linear behavior, which as stated above for STO is indicative of an indirect bandgap for LSAT.…”
Section: Lanthanum Strontium Aluminum Tantalatesupporting
confidence: 92%
“…al. [29] (5.6 eV), but deviates a bit more from other work [30] (5.8 eV). The development of thermally-stable single-crystal rare-earth scandates such as dysprosium scandate, DyScO 3 (DSO), was initially motivated by studies focused on the strain-induced enhancements of superconducting thin films which required an array of substrate materials with a range of available lattice parameters that fit neatly within the window set by STO and barium titanate (3.905 -4.036 Å) [22,23,53].…”
Section: Lanthanum Strontium Aluminum Tantalatecontrasting
confidence: 72%
See 1 more Smart Citation
“…All measurements in this manuscript were performed at room temperature. [40] We point out, however, that Nunley et al [40] observed that LSAT is usually opaque for energies above 4.8 eV, which could account for the extracted gap value here. The absorption edges for the three substrates differ strongly, and the transmittance of the LSAT substrate is markedly different from that of the other two, likely due to defect states in the crystal.…”
Section: Film Growth and Structural Parametersmentioning
confidence: 53%
“…When LSAT is grown on STO, a two-dimensional carrier gas forms at the LSAT/STO interface. 24 LSAT has a band gap of 4.9 eV, 25 smaller than the LAO band gap of 5.6 eV, 26 which can affect the relative importance of the different mechanisms contributing to the formation of the conducting gas. LSAT has a 1 % lattice mismatch with STO, as opposed to a 3 % mismatch in the case of LAO, which means the interfacial STO layers experience a smaller strain in the case of LSAT/STO.…”
mentioning
confidence: 99%